2013
DOI: 10.1179/1751584x13y.0000000037
|View full text |Cite
|
Sign up to set email alerts
|

Review of recent progress in nanoscratch testing

Abstract: Nano-scratch testing, as an important technique for the assessment of the mechanical failure behaviour and adhesion strength of ceramic coatings and a simulation tool of single asperity contact in tribological experiments, is increasingly becoming an established nanomechanical characterisation method. This paper reviews recent work in nano-scratch testing in different engineering applications including thin ceramic films, automotive organic coatings, chemical-mechanical polishing and bio-materials. In the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…The scratch test was used to measure the friction coefficient of the film and to calculate the surface elastic recovery [22]. The single scratch test consisted of three scans along the specimen surface.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The scratch test was used to measure the friction coefficient of the film and to calculate the surface elastic recovery [22]. The single scratch test consisted of three scans along the specimen surface.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…As a compliment to experimental technique, atomistic modeling becomes a powerful tool to deepen the understanding of wear and failure modes of materials at the atomic scale. In the literature, numerous studies of nanoscratching of metals are available both theoretically and experimentally and a comprehensive review can be found in [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of this paper have also performed a more complete characterisation of carbon coatings by combining the results of the nanoindentation tests with additional nanomechanical and nano-tribological test capability, namely nano-scratch, nano-impact and nano-wear [9][10][11]. These tests provided complementary information about the durability of DLC films in these more complex mechanical loading situations.…”
Section: Introductionmentioning
confidence: 99%